Picturing Possibilities: Harnessing Photovoice to Foster Critical Engagement in Youth Facing the Ecological Crisis - Corkery, Anne; Hill, Lauren (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
This participatory action research project used photovoice to explore how adolescents perceive and communicate about the natural world. Members of a high school social justice club took photographs of nature and wrote artist statements to convey their intended messages. They highlighted the beauty and complexity of nature, aiming to inspire appreciation in their audience. Drawing on a participatory paradigm and from concepts of ecopedagogy and self-efficacy, the project underscores the importance of allowing students to experience and express emotions, even negative ones, to challenge the status quo and foster active participation in climate action. The article concludes with recommendations for educators to empower youth in eco-justice efforts.